Trends in the consumption of household durables - Marlena Piekut; Renata Walczak; Barbara Felic; Agnieszka Krzętowska; Magdalena Grabowska; Magdalena Kludacz; Grzegorz Chybicki (Foundations of Management, 2014)
The aim of the paper is the analysis of the household use of durables in Poland and other European countries. Relatively, the highest amount of money for household furnishing with durables was spent by the Bulgarians and the Italians (more than 7% of the total household expenses). In Poland, the highest expenditure occurred for the wealthiest households and those where the head of the household had a university degree while the least money was spent in numerous-family households. The best equipped households (quantity wise) were such that had one or two children and those where the household head had a university degree. The cluster analysis allowed distinguishing household groups of similar durables ownership level. These groups may be treated as consumer segments. The presented analyses also indicate the trends of the Polish consumers regarding the possession of durables.
Keywords: 650; electronic equipment; electronic goods; mobile durables; types of households; Poland; cluster analysis